2021
DOI: 10.1155/2021/6651075
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cell Division Autoantigen 1 (CDA1) in Renal Fibrosis of Diabetic Nephropathy

Abstract: The common kidney disease diabetic nephropathy (DN) accounts for significant morbidity and mortality in patients with diabetes, and its effective diagnosis in incipient stages is still lacking. Renal fibrosis is the main pathological feature of DN. Cell division autoantigen 1 (CDA1), a phosphorylated protein encoded by TSPYL2 on the X chromosome, plays a fibrogenic role by modulating the transforming growth factor-β (TGF-β) signaling, but the exact mechanism remains unclear. TGF-β signaling has been recognized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 117 publications
(146 reference statements)
0
6
0
Order By: Relevance
“…The activated NF-κB pathway in the HSCs is an important signal pathway involved in regulating the immune and inflammatory responses. The main signal target genes downstream of NF-κB signal transduction include the encoding pro-inflammatory factors (such as TNFα, IL-1β, and IL-6), COX2, and anti-apoptotic proteins. Thus, following the same strategy as that of the Nrf2/ARE signaling pathway, we transiently transfect the NF-κB luciferase vector (V15) in HSC-T6 cells (Figure A). We found that the luciferase activity driven by the NF-κB promoter decreased by 40% in the KKP1 treatment group (Figure B–D).…”
Section: Resultsmentioning
confidence: 99%
“…The activated NF-κB pathway in the HSCs is an important signal pathway involved in regulating the immune and inflammatory responses. The main signal target genes downstream of NF-κB signal transduction include the encoding pro-inflammatory factors (such as TNFα, IL-1β, and IL-6), COX2, and anti-apoptotic proteins. Thus, following the same strategy as that of the Nrf2/ARE signaling pathway, we transiently transfect the NF-κB luciferase vector (V15) in HSC-T6 cells (Figure A). We found that the luciferase activity driven by the NF-κB promoter decreased by 40% in the KKP1 treatment group (Figure B–D).…”
Section: Resultsmentioning
confidence: 99%
“…Its limited application is due to its poor permeability and low water solubility. , Considering the peptide p10/OA complex’s ability to permeate cultured HSC-T6 cells, we next looked at its effect on preventing fibrosis. Following the time point of earlier research set, , the cell viability of HSC-T6 treated with peptide p10/OA complex was assessed after 24 or 48 h at mole ratios of 8:4, 8:20, and 8:32 (Figure A). The cell viability of HSC-T6 in the 8:32 group was, however, significantly lower after 48 h than it was at 24 h. Regardless of whether it was 24 or 48 h, we were unable to detect a difference in the level of cell vitality between the 8:4 and 8:20 group (Figure A).…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that the TSPYL2 may be a regulator of apoptosis in the kidneys after IRI as it was demonstrated that TSPYL2 stimulates cell death upon DNA damage 15 and is related to TGF-β-mediated fibrogenesis as well as diabetes-associated renal injury. 22 Therefore, we investigated the role of TSPYL2 in renal IRI using a mouse IRI model and a cell H/R model. Findings of the two models were consistent and showed that TSPYL2 is upregulated upon IRI in mice and H/R injury in the cell line.…”
Section: Discussionmentioning
confidence: 99%